ChemInform Abstract: Regioselective Hydrodebromination of Polybrominated Indoles. Issue 8 (February 2015) - Chelucci, Giorgio; Pinna, Gerard A.; Pinna, Giansalvo
Abstract A reagent combination of NaBH4 and TMEDA in the presence of a Pd‐catalyst is found to be an efficient system for the regioselective hydrobromination of polybrominated indoles having a N‐methyl or N‐methoxycarbonyl substituent.